The Influence Of Instagram Social Media And School Image On Enrollment Decisions At SMP-IT DAR EL-HIJRAH - Shinta Alodia; Vivi Ristanti (LPPM Universitas Buddhi Dharma, 2026)
The development of social media and the importance of school image in the competition of educational institutions have not been fully followed by an increase in student enrollment decisions, as seen in the fluctuations in the number of students at SMPIT Dar El Hijrah. This study aims to analyze the influence of Instagram social media and school image on student enrollment decisions. This study used a quantitative approach with a survey method through questionnaires to 65 respondents with saturated sampling techniques and analyzed using multiple linear regression. The results of the study showed that simultaneously Instagram social media and school image did not have a significant effect on enrollment decisions, but partially school image had a positive and significant effect, while Instagram social media did not have a significant effect, with a determination coefficient value of 8.6% which showed that the influence of variables was still relatively low.